A reform too few or a reform too many: Judicial review, appeals or a prosecutorial system under the UK Competition Act 1998?. (26th June 2020) - Nazzini, Renato
Abstract: This article discusses the Competition and Markets Authority's (CMA) proposals to lower the standard of review of certain antitrust decisions in the Competition Appeal Tribunal (CAT) from a merits appeal to judicial review principles or some other limited basis, while retaining the CAT's 'full jurisdiction' over fines, and to amend the CAT's rules of procedure to restrict the admissibility of new evidence on appeal and the use of oral testimony. The argument developed in this article is that such proposals are: (i) in conflict with the constitutional principle of the rule of law; (ii) incompatible with the Human Rights Act 1998 (HRA98); (iii) a step back even from the often criticized standard of review applied by the Union Courts in respect of European Commission's decisions; (iv) inappropriate as a matter of policy. If the current regime needs improving to reduce the cost and length of the proceedings, then three options should be considered: (i) moving from a merits appeal to a merits review (Option 1); (ii) strengthening the independence of the decision-making panel within the CMA (Option 2), while lowering the standard of review to judicial review principles; (iii) establishing a prosecutorial model (Option 3). Option 3 is the most radical but should be given serious consideration as it is likely to be the best suited to achieving the policy objective of reducing the cost and length of competition proceedings while at the same time retaining rigorous scrutiny of the facts and economic evidence, which is key to ensuring not only the fairness, and therefore the legitimacy, of the system, but also its effectiveness.